Angiosperms of North Andaman, Andaman and Nicobar Islands, India - Raza, S. H.; Kumari, P. V.; Prasad, P. R. C.; Iakshmi, R. K. V.; Reddy, C. S. (Check List, 2009)
The present paper focus on the phytosociological survey carried out in North Andaman part of Andaman and Nicobarislands and enlists the plant species with their habit and forest types they belong. The study area showed five importantforest types viz., evergreen, semi-evergreen, moist deciduous, mangroves and littoral. The survey in these islandsencountered 241 tree species, 119 climbers, 45 shrubs and 49 herbs from 62, 41, 24 and 23 families respectively from asample of 203 quadrats of 0.1 ha size. Euphorbiaceae is found to be dominant family represented by 34 species belongto 21 genera. The result of the survey indicates the potential species richness of the study site that encompasses a vividbiodiversity. It also provides a data base on North Andaman plant species which can be utilized in the context of speciesconservation and future inventories.